2019
DOI: 10.1111/cge.13506
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management in Pitt‐Hopkins syndrome: First international consensus statement

Abstract: Pitt‐Hopkins syndrome (PTHS) is a neurodevelopmental disorder characterized by intellectual disability, specific facial features, and marked autonomic nervous system dysfunction, especially with disturbances of regulating respiration and intestinal mobility. It is caused by variants in the transcription factor TCF4. Heterogeneity in the clinical and molecular diagnostic criteria and care practices has prompted a group of international experts to establish guidelines for diagnostics and care. For issues, for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
168
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(209 citation statements)
references
References 87 publications
6
168
1
7
Order By: Relevance
“…There was no obvious abnormality in the cranial MRI examination of the boy when he was 12 months of age. The boy had a PTHS clinical diagnostic score of 9, which is consistent with the criteria published byZollino et al (2019) for clinical diagnosis of PTHS.A novel heterozygous frameshift variant, c.1973_1974delAC (p.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…There was no obvious abnormality in the cranial MRI examination of the boy when he was 12 months of age. The boy had a PTHS clinical diagnostic score of 9, which is consistent with the criteria published byZollino et al (2019) for clinical diagnosis of PTHS.A novel heterozygous frameshift variant, c.1973_1974delAC (p.…”
supporting
confidence: 81%
“…It has also been reported that patients with nonspecific mild intellectual disability attributable to TCF4 variants have reproduced successfully. However, there have been no reports of individuals with PTHS with nonmosaic TCF4 variants producing children (Sweetser et al, 1993;Zollino et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PTHS was first identified in 1978 by Pitt and Hopkins [1], who described the syndrome in two unrelated patients presenting with a characteristic facial gestalt (comprising a squared forehead, deep-set eyes, a wide mouth, tented upper lip, full lower lip and a broad and/or beaked nasal bridge), developmental delay and abnormal breathing patterns [2][3][4]. Although the definitive prevalence of PTHS is unknown, prevalence estimates lie between 1 in 225,000 and 1 in 300,000 based on the known number of affected individuals [5].…”
Section: Introductionmentioning
confidence: 99%
“…[4,6,9,10], see [7] for a review). The first international consensus statement about PTHS [5] draws together current understanding of these with directions for the diagnosis and management of PTHS. The temperament of individuals with PTHS is often described as amiable and happy, characterised by an "easy-going" demeanour (87%) [5,7] and smiling appearance (89%) [4,6].…”
Section: Introductionmentioning
confidence: 99%